Structural Reforms, Growth and Inequality: An Overview of Theory, Measurement and Evidence - Nauro F. Campos; Paul De Grauwe; Yuemei Ji (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper provides a critical overview of the state of the art in the economics literature on structural reforms. It takes stock of theoretical developments, measurement efforts and of the econometric evidence. We start with a simple theoretical framework for the relationship between structural reforms, economic growth and income inequality. We argue that whether structural reforms have a positive or negative impact depends on various factors. The type of reform, timing, sequence and political constraints play crucial roles in determining the effectiveness of reforms on economic growth and income inequality. We conclude by proposing a 7-point agenda for future research.
Keywords: D60; 330; structural reforms; growth; inequality